GAMIFIKASI DALAM PEMBELAJARAN DI SEKOLAH DASAR - Sri Legowo, Yogi Ageng (Institut Daarul Qur'an Jakarta, Indonesia, 2022)
The game is an interesting activity to study. Not only limited as a fun activity and only done by children, the current dimension of the game is seen as having great potential to achieve learning goals in a fun and meaningful way. This program of implementing games in learning, which is often referred to as gamification, provides a bridge for two different points of view and often creates conflicts between children or students and their parents or teachers. Adults often argue between learning activities and children's play. Although over time, the paradigm has begun to move to become more lenient towards games, and even data has been generated about the benefits of playing in children's learning. But unfortunately the data is still too little for teachers to start implementing games in their learning in the classroom. They need a more complete concept to compose this game-based learning. So this paper provides an overview of the gamification process in learning. It is hoped that the great potential in this game can be utilized by educational practitioners to create effective, fun and meaningful learning.